Gestión administrativa y proceso logístico de la Municipalidad Distrital de Belén Maynas 2021 - Guerrero Culqui, Helmut (2022)
The general objective of the detailed investigation was to determine the relationship between administrative management and logistics processes, the District Municipality of Belén, Maynas 2021, therefore, it has opted for an applied study, descriptive-correlational level and non-experimental design, for which A sample of 32 collaborators has been taken, who were surveyed through a questionnaire. Therefore, the following results were obtained that, the administrative management in the Municipality is classified as deficient, since strategies are almost never established to achieve the objectives established in the entity, on the other hand, rarely the Institutional policies are well defined, for their part, working conditions never allow the development of activities, however, corrective actions are almost never taken. Likewise, the logistics process is classified as regular, since the bidding documents are almost never prepared, however, sometimes the location of the goods is oriented, therefore, the exit control of the goods is almost never carried out. Assets, too, never use physical inventory. Finally, the work concludes that administrative management is related to the logistics process in a considerable and significant way with (rho = .806; sig. = 0.000); as well as with planning (rho = .765; sig. = 0.000); the same happens with organization (rho = .709; sig. = 0.000); the same happens with direction (rho = .738; sig. = 0.000); and the control (rho = .633; sig. = 0.000).